Blended Learning in Learning to Increase the Knowledge of High School Science Students in Kudus - Della Eka Irmayanti; Noorrahma Ika Adiati; Vika Hervi Wihartati; Meilinawati Putri (PT FORMOSA CENDEKIA GLOBAL, 2022)
Learning in the current 4.0 era, especially with the pandemic that is currently hitting Indonesia, requires teachers to carry out various learning innovations, one of the learning methods that can be used in learning innovation, namely blended learning. The purpose of this study was to find out blended learning in learning towards increasing the knowledge of science high school students in Kudus. This type of research is field research, with a quantitative approach. The data collection technique is by distributing questionnaires containing statements, material along with questions and distributed through the Google form. For sampling used purposive sampling. This subject is a high school science student in Kudus. Data analysis used the t test with a significance level of 0.05% assisted by the SPSS 16 program. The results of this study show that blended learning in learning can increase the knowledge of high school science students in Kudus. This research is expected to provide additional information for educators and also become a reference for prospective educators to apply better learning methods.